Capital controls and international financial stability: a dynamic general equilibrium analysis in incomplete markets - Adrian Buss (European Central Bank (ECB), 2013)
In this paper, we conduct an analysis of the implications of capital controls for financial stability. We study a financial transaction (Tobin) tax applicable to cross-border capital flows in a multi-good, multi-country dynamic equilibrium model with incomplete financial markets and heterogeneous agents. The results derived from the model suggest that the impact of capital controls may vary considerably across market segments. In currency markets, capital controls reduce the volatility. However, in international stock markets, their introduction amplifies price movements, thus, increases the volatility; but it reduces a country's vulnerability to external shocks, thereby limiting spillover effects.
Keywords: F21; F31; G12; G15; 330; Capital controls; financial stability; financial transaction (Tobin) tax; General Equilibrium; incomplete financial markets